2017
DOI: 10.1039/c7ra04284a
|View full text |Cite
|
Sign up to set email alerts
|

Removal of heavy metals with sequential sludge washing techniques using saponin: optimization conditions, kinetics, removal effectiveness, binding intensity, mobility and mechanism

Abstract: Testing of sequential sludge washing in triplicate using typical biosurfactant saponin was conducted to remove heavy metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 64 publications
(88 reference statements)
1
36
0
1
Order By: Relevance
“…In the present study, all biosurfactants were used at concentrations above their CMC, which means that micelles were responsible for HM removal. When biosurfactant concentrations are above the CMC, the proposed mechanism of HM removal from soil includes several steps (Chen et al 2008;Tang et al 2017). First, under the conditions of reduced interfacial tension that are present above the CMC, biosurfactant molecules from dissociated micelles can readily adsorb at a soil-water interface.…”
Section: The Effect Of Single Soil Washing With Biosurfactants On Hm mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, all biosurfactants were used at concentrations above their CMC, which means that micelles were responsible for HM removal. When biosurfactant concentrations are above the CMC, the proposed mechanism of HM removal from soil includes several steps (Chen et al 2008;Tang et al 2017). First, under the conditions of reduced interfacial tension that are present above the CMC, biosurfactant molecules from dissociated micelles can readily adsorb at a soil-water interface.…”
Section: The Effect Of Single Soil Washing With Biosurfactants On Hm mentioning
confidence: 99%
“…Hong et al (2002) also used SAP and observed that Pb was more efficiently removed from the exchangeable and carbonate fractions than from the Fe-Mn oxide and organic fractions. RAM and SAP may differ in their ability to remove Pb because the biosurfactants differ in their ability to form complexes with the HM, as the stability constant (log K) of Pb-SAP chelate in aqueous solution is lower (log K[Pb] = 3.91) than that of Pb-RAM chelate (log K[Pb] = 8.58) (Ochoa-Loza et al 2001;Tang et al 2017).…”
Section: The Effect Of Single Washing With Biosurfactants On Hm Distrmentioning
confidence: 99%
“…Currently, biosurfactants have gained much attention due to their advantages over the chemical surfactants in terms of their low toxicity, environmental capability, biodegradability, renewability, availability of natural resources, desirable functionality, and better availability for a wide range of pH values and temperatures [2,3]. Hence, these properties enabled them to be a promising component with a wide range of application in many industries, especially for heavy metal removal in contaminated soil [4][5][6], microbial enhanced oil recovery [7][8][9][10], therapeutic agent in cosmetic and pharmaceutical products [1,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Therefore, a number of methods have been developed for the detection and removal of heavy metal ions from waste and drinking waters. [1][2][3][4][5][6][7][8][12][13][14][15][16][17][18][19] The traditional methods such as ion-exchange, chemical oxidation/reduction, chemical precipitation, ultra-ltration and reverse osmosis have several disadvantages such as high expense, prolonged period with less efficiency, production of other waste products, etc. 19 The adsorption method is still superior to other techniques because of its lowcost, simplicity of design, ease of operation, high effectiveness, reuse of the adsorbents along with their high adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…19 The adsorption method is still superior to other techniques because of its lowcost, simplicity of design, ease of operation, high effectiveness, reuse of the adsorbents along with their high adsorption capacity. [2][3][4][5][12][13][14][15][16]19 However, recent bias has been shied to nanotechnology since nanoscale size, large surface area to volume ratio or efficiency, economic viability and environmental friendliness are all considered useful in the removal of heavy metal ions. 12,19 Recently, magnetic nanoparticles (MNPs) have received attention as adsorbent for the effective removal of metal ions because they can be easily separated by external magnetic eld aer the adsorption process is completed.…”
Section: Introductionmentioning
confidence: 99%